2007
DOI: 10.1007/s10479-007-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic manpower planning model under varying class sizes

Abstract: Solution related to different types of manpower planning problems arising in different industries and organizations are very much helpful for proper planning and implementation of different objectives. Previously those type of problems are mostly solved under the deterministic set up. Gradually several scientists have developed different types of stochastic models appropriate for solving such types of problems. The present study is an attempt to develop a stochastic manpower planning model under the set up whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…The survival of employee in a particular grade is estimated to fulfil without any damage to the organization is considered as the following equation (1)…”
Section: Agoparaju N Vijayasankar Rvinothmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival of employee in a particular grade is estimated to fulfil without any damage to the organization is considered as the following equation (1)…”
Section: Agoparaju N Vijayasankar Rvinothmentioning
confidence: 99%
“…A. K and Gupta. A [1] developed a model based on varying class size and promotion in an organization depending on seniority base through stochastic manpower planning. The researchers concluded that the distribution might change from one organization to another depending on the situation, but the model procedure will remain the same.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many different stochastic manpower planning models have been established and discussed in the literature. For instance, Chattopadhyay and Gupta [2] developed a stochastic manpower planning model under the set up, where the survival rates and the number of workers at different ages are treated as random variables. Yan et al [18] discussed two long-term stochastic demand planning models for air cargo terminal manpower supply planning in long-term operations, where the labor demand is described as a random variable.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the practical application, the problem with time-variant boundaries and time-variant goals should be addressed. The conventional approach to the modeling of the hierarchical manpower system is to employ the methodology of Mehlman (1980), De Feyter (2007 and Chattopadhyay and Gupta (2007). However, in previous research in the field of manpower planning (Mehlman, 1980) it has been indicated that the bare numerical approaches give little insight into the structure of the gained solution.…”
Section: Introductionmentioning
confidence: 99%